Facial mask for prevention of allergic rhinitis symptoms - Oğuz, Oğuzhan; Manole, Felicia; Bayar Muluk, Nuray; Cingi, Cemal (Frontiers in Allergy, 2023)
We reviewed the role of facial masks in preventing allergic rhinitis (AR) symptoms.The literature survey was performed in PubMed, EBSCO, UpToDate, and Proquest Central databases of Kırıkkale University and Google and Google Scholar databases.Results: Aeroallergens are microscopic airborne particles that trigger AR symptoms. In sensitive people, the type 1 hypersensitivity reaction against these allergens occurs when these microparticles enter the nasal mucosa via inhalation. Pollens, molds, dust mites, and animal dander are only some of the allergens suspected of contributing to AR symptoms. The treatment guidelines for AR extensively encompass allergy avoidance and environmental management as the first-line treatment. It is recommended that those who experience seasonal symptoms try to avoid their triggers whenever possible. While medical masks filter out particles larger than 3 micrometers, FFP2 masks are effective against particles as small as 0.004 micrometers. Since both mask types are effective in filtering pollen larger than 5 micrometers in size, they can be used to prevent pollen exposure. The 'antiviral protection' provided by medical and FFP2 masks to hospital employees is roughly equivalent. Thus, both should be effective against direct local (eye) or indirect inhaled (nose, bronchial) pollen exposure. For the masks to do their job, they need to fit correctly.Face mask affects AR patients' quality of life and reduces AR symptoms' severity.